Child abuse: knowledge, awareness, and experience among dentists in India - Bhagya J; Latha Mary Cherian; Pradeesh Sathyan; Sudharani; Rasla P C; Swathi Sanil (Egyptian Journal of Forensic Sciences, 2023)
Abstract Background Medical child abuse and neglect are part of a spectrum of conditions that can lead to significant morbidity and mortality in children. Recognition of these forms of child maltreatment is crucial to prevent harm. Dentists should have familiarity with the framework for diagnosing and reporting child abuse as the orofacial complex is the prime anatomical region to show any signs of abuse. AIM: The purpose of this cross-sectional study was to assess the knowledge, awareness, and experience of dentists in India on child abuse and their role as primary responders. METHODS: A self-administered questionnaire comprising 16 questions was distributed among dentists in India and responses were collected. The questionnaire included questions on the knowledge, awareness, and experience of dentists in child abuse identification, reporting, legal proceedings, and proposals for the betterment of the current scenario. The data collected were statistically analyzed. Results A total of 203 dentists responded to the questionnaires through online platforms. Among them, 78.3% were females, and 65.3% had an institutional practice. While the majority (72.4%) were confident in identifying the indicators of child abuse, the knowledge on reporting was alarming. 98% of participants expressed their need for comprehensive education and training. Conclusion The gap between the knowledge about indicators and the confidence to report suspicious cases are notable in this study. Adequate interventions in the hour of need require the involvement of support agencies and funding at both government and local levels.